Diseño de un sistema de transferencia de calor con aceite térmico para grabación por rodillo en PROQUINAL S.A.S. (2021)
Today where energy is becoming more and more expensive, it is of great importance that companies adopt by making improvements in systems that generate thermal energy. That is why the objective of this project is the design of a heat transfer system with thermal oil to generate recording by rollers to certain vinyl fabrics that are used as the final process in their manufacture. To achieve this objective, two heat transfer systems were studied in depth, first is the system that is currently working, which is a thermal system with steam, and the second is the thermal system proposed in the project, which is with thermal oil, with in order to determine parameters and variables of work in the system and to be able to compare them.